HSP70 family in the renal inflammatory response - Manucha, Walter Ariel Fernando (2014)
Heat shock proteins (HSP) are a shock induced family of proteins, whose most prominent members are a group of molecules dedicated to maintaining the function of other proteins. Interestingly, after being exposed to heat shock typical proinflammatory agonists modify the heat shock-induced transcriptional program and expression of HSP genes, suggesting a complex reciprocal regulation between the inflammatory pathway and that of the heat shock response. The specific task of Heat shock protein 70 (Hsp 70), the most widespread and highly conserved HSP, is to protect against inflammation through multiple mechanisms. So, the expression of immune reactivity to Hsp70 in the kidney could be a cause of hypertension. Hsp70 modulates inflammatory response, as well as down-regulates the nuclear factor kappa-light-chain-enhancer of activated B cells. Also, a decreased expression of renal Hsp70 may contribute to activate the toll-like receptor 4-initiating inflammatory signal pathway.